Hubungan Sanitasi Pasar dengan Tingkat Kepadatan Lalat di Pasar Tradisional Pancur Batu - Nanda, Meutia; Angraini Harahap, Windah; Shafa , Natasya; Nashirah, Sahilatun; Sari Utami, Dwika; Sonia, Azura; Wira Perdana, Sandy; Fachrurrizal (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
A vector is an anthropoid that carries or transmits an infectious agent from an infectious source to a susceptible host. This study aims to understand the relationship between market sanitation and the impact of the number of flies in traditional markets. The design of this research is a qualitative descriptive research that conducts face-to-face visits and the material is in the form of a collection of observations and interviews. The results of this study indicate that there is a very large effect between the density of flies and the prevalence of diarrheal diseases. In traditional markets, among other things, there is a density of flies, namely the level of sanitation in traditional markets which can be seen from the cleanliness of the market and piles of garbage and plant residues from traders, where rot can then occur. ; Go produce an unpleasant odor to detect the presence of flies. This research concludes that there is a relationship between fly density and the prevalence of diarrheal diseases in the Pancur Batu traditional market. Therefore, it is suggested that the Pancur Batu traditional market attracts direct action from the local government to promote cleanliness and implement a clean environment.